La Ética de los contadores en ejercicio profesional del colegio de contadores de la Provincia de Cotopaxi, año 2020. - Guanopatín Villalba, Abigail Estefanía (2021)
The research purpose was to analyze ethical positions of professional accountants of Cotopaxi Province accountants' association against factors that contribute to accounting fraud, for which one quantitative approach and data collection technique were applied through a survey to 173 accounting professionals of the institution, with obtained results it was determined that accountants who practice the profession in Accountants College of Cotopaxi Province are based on deontological ethical stance, which allows them to comply with duties and moral obligations adopting ethics code of Ecuadorian accountants. This research is related to deontological ethical posture because it is responsible for study of duties, obligations and accounting professional behavior in performance on personal and professional activities through norms adoption, principles and rules of an ethical nature, which help to confront any personal relationship in case of fraud. Therefore, this project contributes to improve the situation of economic and financial companies for better making-decision, this means that an accounting professional implies full dedication, responsibility, honesty, and permanent training.